Giving Cucumber Juice to Lower Blood Pressure in Patients with Hypertension at Sarudik Health Center - Ronald Sagala; Rumiris Simatupang (Institute of Computer Science (IOCS), 2020)
Hypertension is still a very important problem for health in the world, even now cases of hypertension are increasing in line with changes in unhealthy lifestyles. In the past, hypertension disease was mostly found in the elderly, but now the prevalence of hypertension cases at a young age is starting to approach cases in the elderly with a still high rate of 25.8%. The impact of hypertension on blood pressure causes damage to the kidneys (kidney failure), heart damage and brain damage (causing stroke). Hypertension can be treated by starting a healthy diet that is rich in fiber and nutrients. The content of cucumber juice is Mg, K, cellulose, H2O. The results of the preliminary survey conducted by the author, obtained information that at the Sarudik Health Center the number of hypertension cases in June 2019 were 29 patients, in July 2019 there were 20 patients. From the results of interviews with 5 hypertensive patients they had never tried cucumber juice, they only avoided high-fat and high-salt foods. Vegetable mentium is not a vegetable that is difficult to find in Central Tapanuli Regency. People may not know or believe that cucumber juice does not increase systole. This study aims to determine the relationship between cucumber juice and systolic reduction in hypertensive patients at the Sarudik Health Center, Pandan District, Tapanuli Tengah District. This research will be able to help hypertensive patients lower their blood pressure. This research is a quasi experimental research. The population in this study were hypertensive patients. The data were collected using a tensimeter before and after being given cucumber juice. The data obtained will be recorded, then analyzed the dependent test pre and post test through the